IMPLEMENTASI MODEL PEMBELAJARAN SELARAS BERBASIS DEEP LEARNING DALAM PEMBELAJARAN IPS UNTUK MENDUKUNG KEMAMPUAN BERBICARA SISWA KELAS II SEKOLAH DASAR - Freisy Sustin Anjelina Bukanaung; Wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Speaking skills are essential competencies that should be developed through active, contextual, and meaningful learning in elementary schools. This study aimed to describe the implementation of the SeLaRAS Learning Model based on the Deep Learning approach in social studies learning to support the speaking skills of second-grade elementary school students. The study employed a qualitative descriptive approach, with data collected through classroom observations, documentation, and field notes during the learning process. The findings indicate that the implementation of the SeLaRAS model provided students with opportunities to connect prior experiences, conduct simple explorations, organize and communicate ideas, and reflect on social values actively. The integration of Deep Learning principles and the four holistic learning dimensions created more meaningful and contextual learning experiences while encouraging students' active participation in speaking activities. The SeLaRAS model has the potential to serve as an innovative alternative for supporting the development of elementary students' speaking skills in social studies learning.